Functions Of The Coordinating Board Of Public Relations In improving democracy (BAKOHUMAS) in Labuhanbatu Selatan - Ependi Pasaribu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Public relations is an activity that is carried out and planned on an ongoing basis in order to create and maintain mutual understanding. Its main purpose is to provide information to the widest possible public. With this information openness can be new knowledge and new learning for the community. Bakohumas own activities in the South Labuhanbatu KPU are also aimed at providing the widest possible understanding of electoral and political education for the sake of better democracy in South Labuhanbatu Regency